Impact of the student’s household budget on the selection of a given major at post-graduate studies - Barańska, Magdalena (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2017)
The aim of this paper is to present the results of the empirical research conducted among students of post-graduate programmes offered in English at the Wrocław University of Economics. The questionnaire survey was to answer the research questions about whether the price of post-graduate studies has any impact on the student’s household budget and if so, how high the impact is, and what impact the fee paid for the post-graduate studies has on the selection of a given major. At the same time, it was attempted to determine whether there is any financial added value (e.g. in the form of a pay rise) after completing post-graduate studies and if so, what impact it has on the student’s selection of a major. When endeavouring to answer the questions asked, literature studies in the area of budget were carried out and a questionnaire survey, supported with an interview with post-graduate students, was conducted
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics, 2017, Nr 474, s. 173-184
Keywords: budget; household budget; post-graduate studies; budżet; budżet domowy; studia podyplomowe